La vie humaine au rythme des saisons et des mois – Les Quatre âges de l’homme de Philippe de Novare et Les Douze mois figurez - Loba, Anna (Studia Romanica Posnaniensia, 2021)
The division of human life into ages is not only a sociological issue but also includes a philosophical, moral and religious reflection. The relationship between human life and the course of the year punctuated by the seasons and months has not remained without influence on the very notion of the ages of life. The question that arises is whether we can harmonize the unpredictable flow of human life with the calendar. The confrontation of two medieval works which develop this parallel: the treatise by Philippe de Novare Les Quatre âges de l’homme, and the anonymous poem Les Douze mois figurez, should provide an answer to this question.